Depression in Woman Breast Cancer: Literature Review - Endrat Kartiko Utomo; Totok Wahyudi; Sinta Dwi Anggraini; Sitti Rahma Soleman (Proceeding of International Conference on Science, Health, And Technology, 2021)
Depression is psychological distress often occurred on cancer patient. Depression can increase perception pain, inhibits healing process, and also increases burden patient with cancer. Breast cancer can affect a woman’s self-image, it is considered a painful experience and may lead to psychological reactions such as depression. The purpose of this study was to review depressive condition in woman breast cancer in Indonesia. The search method for relevant article uses the database PubMed, Science Direct and Google Scholar using the keyword depression, breast cancer, woman Indonesia. Seven articles was included in the literature review. Age of woman with breast cancer in the selection range from 45 to 59 years. Based on the research objectives, there were seven studies that qualified for literature review and identified from seven studies found two types of articles that indicated a degree of major depression. Two types of articles indicate a moderate degree of depression. And three articles indicated a low depression level. Depressions in Indonesian woman still low. However, these results need to be confirmed at a later date to improve evidence-based nursing and need to research in the future, which based on the stage levels of breast cancer.